PENGARUH SELF-DIAGNOSIS SHEET TERHADAP PENINGKATAN HASIL BELAJAR GERAK LURUS PESERTA DIDIK KELAS X SMA - Ira Irawan; Edy Tandililing; Syukran Mursyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to determine the effectiveness of self-diagnosis sheet on linear motion towards students’ study result at class X SMA Santo Fransiskus Asisi. The form of this research is pre-experimental design with one group pretest-posttest design. The tools of data collection is essay test with five questions. The sample of the research was chose by using purposive sampling technique. The students’ study result that analysed through N-gain formula had increased 0.641 (medium). It was found that the average percentage of students’ study result before using self-diagnosis sheet was 46% and after the use of self diagnosis sheet is 80%. The use of self-diagnosis sheet is effective to increase students’ study result with effect size score obtained 1.520 (high). The result of this research is expected can be used as an alternative learning activity to increase students’ study result. Keywords: Effect, Study Result, Linear Motion, Self-Diagnosis Sheet.